1996
DOI: 10.1007/bf02238545
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent compressive load stimulates osteogenesis and improves osteocyte viability in bones cultured “in vitro”

Abstract: The effect of mechanical stresses on osteogenesis, the viability of osteocytes and their metabolic activity in organ culture of bones intermittently loaded "in vitro" are reported. Metatarsal bones, isolated from 12-day-old rats, were cultured in BGJb medium (with 10% foetal calf serum, 75 micrograms/ml of ascorbic acid, 100 U/ml of penicillin and 100 micrograms/ml of streptomycin), in humidified air enriched by 5% CO2 and 30% O2, and loaded in our original device for 1/2 an hour at 1 Hz. homotypic isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
5
24
0
1
Order By: Relevance
“…Osteocytes are terminally differentiated osteoblasts, which become encased in the mineralized matrix during bone formation (46). The functional role of the osteocyte remains unclear; however, they can communicate through dendritic processes and have been theorized to be the primary sensors of mechanical strain in bone (47)(48)(49). We confirmed the expression within osteocytes at the protein level by immunohistochemistry.…”
Section: Expression Of Of45 In Bone Marrowsupporting
confidence: 58%
“…Osteocytes are terminally differentiated osteoblasts, which become encased in the mineralized matrix during bone formation (46). The functional role of the osteocyte remains unclear; however, they can communicate through dendritic processes and have been theorized to be the primary sensors of mechanical strain in bone (47)(48)(49). We confirmed the expression within osteocytes at the protein level by immunohistochemistry.…”
Section: Expression Of Of45 In Bone Marrowsupporting
confidence: 58%
“…We (1) and others (5-7) demonstrated that fluid flow increases gap junction expression and function in osteocytic mouse long bone osteocyte (MLO-Y4) cells; however, Thi et al (41) demonstrated that fluid flow decreases gap junction function and expression in MLO-Y4, emphasizing the need for additional examination of this issue. In vivo, Lozupone et al (30) demonstrated that mechanical loading of rat metatarsal bones increased the incidence of osteocytic gap junctions, and we demonstrated that expression of Cx43 by osteocytes is increased in areas of bone exposed to tension relative to areas exposed to compression or to control bone (39).…”
supporting
confidence: 62%
“…However, this strain-derived flow, for which experimental evidence is reported by Knothe Tate et al (42) and Knothe Tate and Knothe, (43) may not only act as the mechano-signal-multiplying system of bone but also may improve osteocyte viability by facilitating exchange of nutrients and waste products. (44,45) Similarly, this mechanism may be crucial in the transport of the hypothetical phosphate-regulating factor to the osteocytes, where it is to be activated/deactivated by Phex. Therefore, it would be interesting to study whether immobility leading to decreased canalicular fluid flow also leads to disturbed phosphate metabolism and hypophosphatemia.…”
Section: Westbroek Et Almentioning
confidence: 99%